2015
DOI: 10.1177/1934578x1501001151
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-inflammatory Activities of Essential Oil and Extracts of Piper miniatum

Abstract: The chemical composition of the essential oil and antioxidant and anti-inflammatory activities of the extracts from Piper miniatum were determined. GC and GC-MS analysis of the essential oil resulted in the identification of 64 components, accounting for 89.2% of the total. The major components were caryophyllene oxide (20.3%) and α-cubebene (10.4%). The antioxidant activity was evaluated by β-carotene/linoleic acid bleaching, DPPH radical scavenging and total phenolic content. In the β-carotene assay, the n-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…On the other hand, NO has been proposed as a host anti-microbial system (Akaiker and Maeda, 2000). Production of Nitric oxide is initiated in by inducible nitric oxide synthases (iNOS) in activated macrophages and neutrophils during defense and immunological reactions (Salleh et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, NO has been proposed as a host anti-microbial system (Akaiker and Maeda, 2000). Production of Nitric oxide is initiated in by inducible nitric oxide synthases (iNOS) in activated macrophages and neutrophils during defense and immunological reactions (Salleh et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The sesquiterpene α-copaene, which was present at over 10% in the P. bellidifolium oil, has also been reported as a major constituent of P. boehmeriafolium oil (28.3%) from Vietnam (Hieu et al 2014). Aromadendrene was another sesquiterpene present in significant proportion in P. belldifolium and has been reported as a major constituent of the leaf oils of P. gaudichaudianum (15.55%) from the state of Rondônia, Brazil (Morais et al 2007) and P. muricatum (16.2%) from Malaysia (Salleh et al 2015). The sesquiterpene γ-cadinene has been characterized in the leaf oil of P. hispidum (25.13%) from the state of Rondônia, Brazil (Machado et al 1994) and P. cubeba (16.6%) from Indonesia (Bos et al 2007) in larger quantities than that found by us in the oil of P. consanguineum.…”
Section: Resultsmentioning
confidence: 96%
“…The reagents were prepared according to the standard protocol (Lipoxygenase inhibitor screening assay kit, Item No. 760700 Cayman Chemicals Co) [7][8][9]. Stock solutions of samples were prepared so as to obtain various concentrations (extracts: 1000-62.5 μg/mL; compounds 100−6.25 µM) in the respective wells.…”
Section: Methodsmentioning
confidence: 99%